2018
DOI: 10.1186/s12880-018-0252-x
|View full text |Cite
|
Sign up to set email alerts
|

Automatic brain tissue segmentation based on graph filter

Abstract: BackgroundAccurate segmentation of brain tissues from magnetic resonance imaging (MRI) is of significant importance in clinical applications and neuroscience research. Accurate segmentation is challenging due to the tissue heterogeneity, which is caused by noise, bias filed and partial volume effects.MethodsTo overcome this limitation, this paper presents a novel algorithm for brain tissue segmentation based on supervoxel and graph filter. Firstly, an effective supervoxel method is employed to generate effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Currently, Numerous methods and algorithms have been proposed to reduce metal artifacts in CT and CBCT images [2326]. Y. Chen et al, [23] showed that A discriminative dictionary representation method was developed to mitigate CT truncation artifacts directly in the DICOM image domain. Both phantom and human subject studies demonstrated that the proposed method can effectively reduce truncation artifacts without access to projection data.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Numerous methods and algorithms have been proposed to reduce metal artifacts in CT and CBCT images [2326]. Y. Chen et al, [23] showed that A discriminative dictionary representation method was developed to mitigate CT truncation artifacts directly in the DICOM image domain. Both phantom and human subject studies demonstrated that the proposed method can effectively reduce truncation artifacts without access to projection data.…”
Section: Discussionmentioning
confidence: 99%
“…These models divided the brain image into multiple regions. For example, [40,41] divided the brain into eight regions), whereas [42,43] divided the brain into three regions. Dolz et al [44] proposed 3D and fully CN N for the segmentation of the subcortical brain structure.…”
Section: Brain Segmentationmentioning
confidence: 99%
“…The used BrainWeb data set consists of artificially simulated MRI data and was originally designed to validate various segmentation algorithms as a known basic truth [20]. It exhibits similarity of image morphological structures to in vivo acquired MRI data [20,38] and is used frequently in studies for verification purposes [1,16,19].…”
Section: Limitations Of the Studymentioning
confidence: 99%